An Introduction to Animal Farming System in India. - SINGH, VEER (The Indian Journal of Animal Sciences, 2013)
First Edition: 2012. Chief editor: Professor (Dr) R. NagercenkarPublishers: Navbharath Press. No. 10, Sirur Park, ‘B’ Street, Seshadripuram, Bengaluru-560020. 080-23561142. ISBN: 97881-89650-22-3.Price: Rs. 3900 (India).US $ 156 (Abroad). pages: 898.